Insights into the assessment of the magnetic-field-induced precipitation behavior of alloy carbides M7C3 in steels. (September 2022) - Zhang, Dong; Hou, Tingping; Liang, Xuan; Zheng, Peng; Luo, Weidi; Lin, Hengfu; Xiao, Xiangheng; Wu, Kaiming
Graphical abstract: Highlights: The 3d orbit of Fe in triangular prism contributes to the self-magnetic moment. The magnetic-field-induced Curie temperature shifts to higher temperature. Magnetic Gibbs free energy reduction resulted in M7 C3 precipitation in advance. Abstract: A combination of first-principles calculations, Weiss molecular field theory and density functional perturbation theory is combined to systematically evaluate the magnetic-field-induced thermodynamic properties of the alloy carbide M7 C3 in steel. Special emphasis is focused on the self-magnetic and the external magnetic-field-induced magnetic contribution determined by extending the magnetic heat capacity. The self-magnetism origins from the 3d orbit contribution of the Fe atoms which constituted the carbon-containing trigonal prism. The magnetic-field-induced Curie temperature which triggers the boundary of the long and short-range magnetic order closely related to the Cr content and the magnetic field strengths. The higher external magnetic-field-induced Gibbs energy change provides a potential precipitation strategy in advance for the alloy carbides M7 C3 which is well in agreement with the experimental results. Our insights further will extend the mechanistic understanding of magnetic-field-induced phase transformation in ferromagnetic Fe-based alloys, emphasizing the role of external field in minimizing energy and guiding new alloy design.